Ventilation Rate and Thermal Environment Properties of Double Skin Façade Considering Wind Profile and Direction. Issue 3 (1st September 2017) - Kim, Geum-Hee; Kwon, Hyuk-Min; Yang, Jeong-Hoon
Abstract : This study analyzes the impact of a windy environment on the ventilation rate and the thermal environment of a double skin façade (DSF). The wind profile was used to change the direction of the wind to the front, back, and side directions. Three cases were examined using computational fluid dynamics (CFD) analysis. There were two openings on the front of the DSF in Case 1, openings on the lower and front parts of the DSF in Case 2, and two openings on the front of the DSF for each story in Case 3. The results are as follows. 1) The front wind direction interrupted the release of the cavity′s interior air, and the ventilation rate decreased by an average of 47.6% in comparison to the results with wind from the side and back directions. 2) The ventilation rate was highest for the back direction in Cases 1 and 3 and for the side direction in Case 2. The ventilation rate of Case 3 was the lowest. 3) The total heat transfer rate of the highest story of the DSF was inversely proportional to the ventilation rate.